2022
DOI: 10.1136/spcare-2022-003622
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care phenotypes among critically ill patients and family members: intensive care unit prospective cohort study

Abstract: ObjectiveBecause the heterogeneity of patients in intensive care units (ICUs) and family members represents a challenge to palliative care delivery, we aimed to determine if distinct phenotypes of palliative care needs exist.MethodsProspective cohort study conducted among family members of adult patients undergoing mechanical ventilation in six medical and surgical ICUs. The primary outcome was palliative care need measured by the Needs at the End-of-Life Screening Tool (NEST, range from 0 (no need) to 130 (hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Although the NEST minimal clinically important difference is unclear, such a targeted difference is significantly associated with clinically important changes in depression and anxiety symptoms, goal concordance, and quality of communication as well as an item threshold value in our recent latent class analyses of serious need. [29][30][31][32] Hierarchical linear models were used to estimate the treatment effect on changes in NEST scores, as well as to account for the association of both family members' repeated measurements over time and between family members with the same clinician (ie, clustering). Models were fit in SAS PROC MIXED software version 9.4 (SAS Institute), assuming a compound symmetry covariance structure for the repeated measures and a random variance component for the clustering (eAppendix 7 in Supplement 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the NEST minimal clinically important difference is unclear, such a targeted difference is significantly associated with clinically important changes in depression and anxiety symptoms, goal concordance, and quality of communication as well as an item threshold value in our recent latent class analyses of serious need. [29][30][31][32] Hierarchical linear models were used to estimate the treatment effect on changes in NEST scores, as well as to account for the association of both family members' repeated measurements over time and between family members with the same clinician (ie, clustering). Models were fit in SAS PROC MIXED software version 9.4 (SAS Institute), assuming a compound symmetry covariance structure for the repeated measures and a random variance component for the clustering (eAppendix 7 in Supplement 2).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, outcomes such as palliative care needs that are more temporally proximate to intervention and assess several domains of palliative care may better reflect intervention mechanisms and the time frame of greatest clinical importance to the patient, family member, and clinician . In addition to its responsiveness to change, the NEST can also serve as a screening tool given the poor predictive value of clinical characteristics, as well as a means by which to identify patients and family members with complex communication needs who may potentially be best served by specialists or to direct nonphysician multidisciplinary practitioners to those with specific needs aligned with their expertise …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional barriers we identified also align with other studies, including perceptions that the treating teams are self-sufficient and can provide satisfactory palliative care independently, and that patients and families may resist involvement of the palliative care team. 25 Despite palliative care improving outcomes for Open access individuals at the end of life, many patients who could benefit from palliative services (eg, those with complex communication needs, spiritual and cultural needs, and high stress needs 26 ), do not receive timely consultations. [27][28][29] A survey of 133 healthcare professionals from a private hospital in Australia reported that nearly 40% of dying patients received palliative care 'sometimes, rarely or never'.…”
Section: Discussionmentioning
confidence: 99%